Loss of Nogo receptor homolog NgR2 alters spine morphology of CA1 neurons and emotionality in adult mice - Borrie, Sarah C.; Sartori, Simone B.; Lehmann, Julian; Sah, Anupam; Singewald, Nicolas; Bandtlow, Christine E. (Frontiers in Behavioral Neuroscience, 2014)
Molecular mechanisms which stabilize dendrites and dendritic spines are essential for regulation of neuronal plasticity in development and adulthood. The class of Nogo receptor proteins, which are critical for restricting neurite outgrowth inhibition signaling, have been shown to have roles in developmental, experience and activity induced plasticity. Here we investigated the role of the Nogo receptor homolog NgR2 in structural plasticity in a transgenic null mutant for NgR2. Using Golgi-Cox staining to analyze morphology, we show that loss of NgR2 alters spine morphology in adult CA1 pyramidal neurons of the hippocampus, significantly increasing mushroom-type spines, without altering dendritic tree complexity. Furthermore, this shift is specific to apical dendrites in distal CA1 stratum radiatum. Behavioral alterations in NgR2-/- mice were investigated using a battery of standardized tests and showed that whilst there were no alterations in learning and memory in NgR2-/- mice compared to littermate controls, NgR2-/- displayed reduced fear expression in the contextual conditioned fear test, and exhibited reduced anxiety- and depression-related behaviors. This suggests that the loss of NgR2 results in a specific phenotype of reduced emotionality. We conclude that NgR2 has role in maintenance of mature spines and may also regulate fear and anxiety-like behaviors.